[View of Chorro and Monterey from Mission San Luis Obispo] (1940)
View standing from Mission grounds looking towards Monterey and Chorro streets. Visible in foreground are blossoming Century Plants (Agave americana). The building on the right is Mission Garage (former French Hotel), and in the center of the photo is 837 Monterey, which at the time was Wickenden's. The wood-sided building on the left edge is M. Lewin Building at 792 Monterey. The year 1940 is written on the back of 168-6-d-12-21-03, taken at the same time.